Resource extraction, greenhouse emissions, and banking performance. (December 2022) - Su, Chi-Wei; Mirza, Nawazish; Umar, Muhammad; Chang, Tsangyao; Albu, Lucian Liviu
Abstract: The extraction of natural resources is responsible for more than fifty percent of the global emissions and biodiversity damage. The phenomenon is more profound in emerging markets with predominant reliance on natural resources for economic growth and warrants immediate attention. Such economies have multiple constraints including their over dependence on banking sector for corporate financing. However, this dependence provides an opportunity to financial intermediaries to facilitate the promotion of circular economy and sustainable business models. In this research, we explore inherent incentives for the banking sector to limit their exposure to high emitters. Using a sample of 290 banks in twenty emerging countries for over ten years, we assess the relationship between lending to resource emitters, banking spread, and default likelihood. Our results show a negative link between loans to high emission firms and banking spreads. Similarly, we observe that the default likelihood will increase with an increase in polluting borrowers. These findings demonstrate that limiting the lending to resource emitters incentivizes the banking firms, and consequently these intermediaries can assist in achieving sustainability goals through their credit practices. Highlights: The study explores inherent incentives for the banking sector to limit their exposure to high emitters. The study used a sizeable sample of banks in twenty emerging countries for over ten years. The study assesses the relationship between lending to resource emitters, banking spread, and default likelihood. The results show a negative link between loans to high emission firms and banking spreads. The results also observe that the default likelihood will increase with an increase in polluting borrowers.